Customer Relationship Management in Banking Sector: A Study on Bank Employees Perception about Customers in Tirunelveli District - Kumar, A. Senthil; Soundararaja, Dr. K. V. (SMART MOVES JOURNAL IJELLH, 2019)
The purpose of business is to create new customers and retain old customers. Customer orientation is the ultimate key to success of any business. Customer Relationship Management (CRM) is a comprehensive approach for creating, maintaining and expanding customer relationships. CRM does not just belong to sales and marketing rather it is an intelligent blend of marketing and information technology for serving the customer with greater care and value. The data required for this study had been obtained from primary and secondary sources. First hand data were collected from the bank employees directly through structured comprehensive interview schedule. As the population size is infinite, 333 respondents are selected as sample among the population using stratified random sampling. The sample has been stratified as 248 employees from public sector banks and 85 employees from private sector banks in Tirunelveli district. It is found that fund transfer under ECS and collection of negotiable instruments are the important perception towards the dimension of CRM practices under banking services among the employees of public sector banks whereas the important perception towards the dimension of CRM practices under banking services among the employees of private sector banks are portfolio management and acting as trustee executor and administrator.